Challenges in Managing Acute ST Myocardial Infarction in Community Heart Hospital - Dhungel, Sachin; Gautam, Samir; KC, Bishal; Khan, Mazhar; Yadav, Umesh; Gyawali, Asmita; Dhungel, Mandip; Bhusal, Ramesh (Journal of National Heart and Lung Society Nepal, 2023)
Background:The financial issue can cause pre-hospital delay, choosing reperfu-sion therapy and delay in door to balloon or door to needle time during early management of STMI. The objective of this research is to study the in-hospital cost for STMI patients in community hospital. Methods: This cross sectional observational study was done for two years from September 2019 to August 2021. Total in hospital host (in Nepalese rupees) dur-ing managing STMI was calculated. Results: The mean in-hospital cost of managing STMI (intervention or medical management) was 78,585±71167. For Intervention the total mean cost was 1,73,884±137551 of which PPCI with one stent 1,80,972±25547 and Percutane-ous old balloon angioplasty (POBA) 1,37,551 ±34824. For medical manage-ment, the total mean cost was 32,001 ±19442 of which thrombolysis 36069±24188 while conservative management was 31488±18765. Conclusion: The in hospital cost was more for intervention management com-pared to medical therapy. The mortality was more for the medical therapy com-pared to intervention. Cost of life saving procedures like reperfusion therapy in STMI need to be make more affordable. Patient education for early use of nearby available cardiac facilities including Cath lab need to be promoted.